EARLY VS LATE CAFFEINE THERAPY IN PRETERM INFANTS: ANALYSIS OF CLINICAL OUTCOME - Niaz, Hafsa; Jalil, Jawad; Adil, Muhammad; Basheer, Faisal; Akhtar, Shahzad; Hamid, Naila (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study clinical outcome of early versus late caffeine therapy in preterm infants. Study Design: Prospective comparative study. Place and Duration of Study: Neonatal Intensive Care Unit, Pak Emirates Military Hospital, Rawalpindi, from Jan to Jul 2018. Methodology: A total of 40 preterm infants with gestational age <32 weeks and birth weight <1500 grams were randomly divided into two groups on the basis of initiation of caffeine therapy i.e. group A (early caffeine group) and group B (late caffeine group). Infant’s demographic data and clinical outcomes were compared between both groups using SPSS IBM software. Results: Mean gestational age was 29.9 ± 1.19 weeks with male to female ratio of 1.5:1 Mean birth weight was 1165.3 ± 316 grams. Half (50%) of the infants were delivered by cesarean section while surfactant was given in 29 (72.5%) infants. While comparing both groups we observed that early caffeine shortens duration of Neonatal Intensive Care Unit stay (p<0.05) whereas caffeine therapy initiation timings didn’t influence the risk of development of Respiratory Distress Syndrome or need of mechanical ventilation. Conclusion: Early caffeine therapy in preterm infants is associated with decrease duration of Neonatal Intensive Care Unit stay. However further work is needed in this regards to establish its efficacy and safety.